2017
DOI: 10.3389/fnhum.2017.00211
|View full text |Cite
|
Sign up to set email alerts
|

Brain Gray Matter Atrophy after Spinal Cord Injury: A Voxel-Based Morphometry Study

Abstract: The aim of this study was to explore possible changes in whole brain gray matter volume (GMV) after spinal cord injury (SCI) using voxel-based morphometry (VBM), and to study their associations with the injury duration, severity, and clinical variables. In total, 21 patients with SCI (10 with complete and 11 with incomplete SCI) and 21 age- and sex-matched healthy controls (HCs) were recruited. The 3D high-resolution T1-weighted structural images of all subjects were obtained using a 3.0 Tesla MRI system. Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
56
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(72 citation statements)
references
References 55 publications
(86 reference statements)
12
56
3
1
Order By: Relevance
“…Using the same technique in the very same cohort, the authors observed also myelin reduction in thalamus, cerebellum and brainstem in the same period of time (Freund et al, 2013;Grabher et al, 2015). These combined morphometry and tissue property findings in the early injury phase contrast with the absence of volume differences when comparing sub-acute (duration <1 year) and chronic (duration >1 year) patients with complete motor SCI (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Using the same technique in the very same cohort, the authors observed also myelin reduction in thalamus, cerebellum and brainstem in the same period of time (Freund et al, 2013;Grabher et al, 2015). These combined morphometry and tissue property findings in the early injury phase contrast with the absence of volume differences when comparing sub-acute (duration <1 year) and chronic (duration >1 year) patients with complete motor SCI (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 71%
“…One of the well-established methods -voxel-based morphometry (VBM), was used to monitor local grey matter volume changes following SCI to deliver conflicting results ranging from lack of SCI related brain anatomy changes (Crawley et al, 2004) to evidence about profound sensorimotor cortex reorganization (Jurkiewicz et al, 2006;Wrigley et al, 2009a;Henderson et al, 2011;Freund et al, 2013). More recent reports demonstrate grey matter loss in nonmotor areas including anterior cingulate gyrus, insula, orbitofrontal gyrus, prefrontal cortex and thalamus (Wrigley et al, 2009b;Grabher et al, 2015;Chen et al, 2017). One of the potential reasons for the reported controversial findings is the fact that these studies pooled together patients with incomplete and complete SCI (Crawley et al, 2004;Jurkiewicz et al, 2006;Chen et al, 2017) not taking into account potential impact of differences in the time span since injury (Grabher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal cord injury causes widespread structural and functional abnormalities in brain regions such as the primary motor cortex, primary somatosensory cortex, medial prefrontal cortex (PFC) and adjacent anterior cingulate cortex, causing a decrease in the volume of grey matter. Moreover, owing to the reduced volume of grey matter, structural abnormalities are observed in the corticospinal and corticopontine tracts (Chen et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, only a few works have focused on the possible effects of SCI on the upper nervous system, such as brain regions that control learning and memory/cognition or emotions. Although clinical evidence shows significant neurodegenerative changes, recent magnetic resonance imaging studies propose that SCI can cause investigable and vast changes in the brain (Chen et al., 2017). Recently, Wu et al.…”
Section: Introductionmentioning
confidence: 99%